Combination of Selected MET and EGFR Inhibitors Decreases Melanoma Cells’ Invasive Abilities - Simiczyjew, Aleksandra; Pietraszek-Gremplewicz, Katarzyna; Dratkiewicz, Ewelina; Podgórska, Marta; Matkowski, Rafał; Ziętek, Marcin; Nowak, Dorota (Frontiers in Pharmacology, 2019)
We have previously shown that combination of foretinib, an inhibitor of MET (hepatocyte growth factor receptor), with gefitinib or lapatinib, inhibitors of EGFR (epidermal growth factor receptor), has a synergistic cytotoxic effect on melanoma cells. However, there are cancer cells resistant to drugs’ treatment which are still able to invade. Thus, in this study we examined the influence of these drugs on invasive abilities of melanoma cells. To investigate cell migration and invasion Transwell inserts, and wound healing assay were used. Cell viability was evaluated by XTT method, while invadopodia formation by immunocytochemistry. Level of phosphorylated Src kinase (pSrc) was verified by Western blot. Proteolytic activity of cells was analyzed using gelatin conjugated with fluorescein degradation assay and gelatin zymography. Combination of used inhibitors diminished cell movement, resulting in smaller distances covered by cells and decreased the ratio of cells with ability to cross the Transwell inserts. These inhibitors induced changes in formation of invadopodia and actin cytoskeleton organization. Their application also decreased the level of pSrc kinase. Furthermore, used drugs led to reduction of proteolytic activity of examined cells. Our data support the idea that simultaneous targeting of EGFR and MET could be a promising therapeutic strategy inhibiting not only tumor cell growth, but also its metastasis.